2005
DOI: 10.1136/pgmj.2004.031104
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopy waiting times and impact of the two week wait scheme on diagnosis and outcome of upper gastrointestinal cancer

Abstract: The NHS has introduced the two week wait scheme to detect upper gastrointestinal cancers at an early stage and improve survival rates The aim of this study was to assess the impact of this scheme and changes in endoscopy waiting times on tumour stage and resection rates over a four year period. Data were analysed prospectively for all patients diagnosed with oesophagogastric cancer between September 1998 and September 2002 and from those referred under the two week wait scheme since its introduction in 2000. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 3 publications
1
17
0
Order By: Relevance
“…This should, in theory, have a negative impact on all other aspects of the service, although no evidence of this has been found to date. Three studies reported a decline in the routine endoscopy waiting lists following the introduction of the TWR [11,25,45], possibly due to an increased awareness of the guidelines for patient referrals, the more efficient organisation of services or the introduction of nurse endoscopists to cope with increased demand.…”
Section: Discussionmentioning
confidence: 99%
“…This should, in theory, have a negative impact on all other aspects of the service, although no evidence of this has been found to date. Three studies reported a decline in the routine endoscopy waiting lists following the introduction of the TWR [11,25,45], possibly due to an increased awareness of the guidelines for patient referrals, the more efficient organisation of services or the introduction of nurse endoscopists to cope with increased demand.…”
Section: Discussionmentioning
confidence: 99%
“…With little evidence that '2-week wait' initiatives impact on survival, 15,16 and growing pressure to find alternative mechanisms of improving services in general, onestop approaches are al ogical progression.…”
Section: Discussionmentioning
confidence: 99%
“…However, the importance of medical delays for chronic diseases including cancer is inconclusive. Most studies found null impact of waiting time on cancer specific survival, including gastro-esophageal [7, 8, 16], colorectal [19], lung [20], and pancreatic [6] cancers. Other studies claimed however that a detrimental effect on the prognosis could be introduced if certain waiting time threshold was exceeded.…”
Section: Discussionmentioning
confidence: 99%
“…This was true even for relatively aggressive cancers, e.g. esophageal, gastric cancers [7, 8] and pancreatic cancer [6]. Yet, whether or not shorter waiting time for treatment influences other domains of cancer patients’ overall well-being is to a large extent unknown.…”
Section: Introductionmentioning
confidence: 99%